Regional Mapping Based on Tourism Destinations in West Java: K-Medoid Clustering Analysis - Almajid, Nafis; Dina Atika, Prima; Fadhilla Ramdhania, Khairunnisa (School of Computing, Telkom University, 2024)
The growth of the tourism sector in West Java demands an optimal development strategy. This study aims to cluster regions in West Java based on the characteristics of their tourist destinations using the K-Medoid algorithm. This algorithm was chosen because of its superiority in producing optimal clusters and robustness to outliers. Data on tourist destination characteristics were analyzed using the K-Medoid algorithm and the Elbow method to determine the optimal number of clusters. As a result, three clusters with different characteristics were formed. The first cluster,